Evaluation of previous management against a developed clinical pathway for chronic rhinosinusitis with nasal polyposis in Universiti Kebangsaan Malaysia Medical Center. Issue 44 (5th November 2021) - Wong, Timothy LW; Husain, Salina; Ismail, Aniza; Zahedi, Farah Dayana; Aljunid, Syed Mohamed; Nur, Amrizal Muhammad
Abstract : Abstract: The study aims to evaluate previous management of CRSwNP patients in Universiti Kebangsaan Malaysia Medical Center (UKMMC) against a developed CP. Chronic rhinosinusitis with nasal polyposis (CRSwNP) has high economic burden and impacts patient's quality of life. Implementation of clinical pathway (CP) can standardize care while optimizing resources. Analytical cross-sectional This study utilized medical records of 103 CRSwNP patients at UKMMC otorhinolaryngology clinic from 2010 to 2015. Patients were divided into groups who underwent or did not undergo surgery. Information was obtained regarding sociodemographic, follow-ups, pharmaceutical regimes, and treatment cost. Cost analysis was done using top-down analysis and activity-based costing and CP was formulated. Cost was calculated using year 2020 rates to adjust for inflation. (United States Dollars [USD]1 = Ringgit Malaysia [RM] 4.2015) Study showed non-CP patients were undertreated compared to CP. This affects clinical outcomes as optimal treatment demanded by CP was not achieved. Total cost for non-CP, non-surgery patients were lower (USD660) compared to CP (USD780) due to under treatment and shorter follow-ups. Meanwhile, total cost for non-CP surgery patients were higher (USD3600) compared to CP (USD2706) due to longer visit durations and hospital stays. Non-CP surgery group underwent lengthy follow-up duration (20.7 months) prior to operation compared to 12 months expected in CP. Study showed non-CP patients were undertreated compared to CP. We identified aspects which resulted in resource wastage and unnecessary burden to our healthcare system. This study enables development of a written CP by fine-tuning various aspects of CP which could be applied to our future practice.